Intestinal Helminth Infections and Their Association with QuantiFERON-TB Gold Plus Test Performance in an Endemic Setting, Northwest Ethiopia - Zenebe, Yohannes; Abebe, Markos; Munshea, Abaineh; Yismaw, Gizachew; Zewde, Meaza; Alemayehu, Mekdelawit; Lang, Roland; Habtamu, Meseret (Infection and Drug Resistance, 2024)
Background: Timely detection and treatment of latent TB infection (LTBI) is part of WHO’s strategy against tuberculosis (TB). Helminth infections can modulate immune responses, potentially impacting the performance of interferon-gamma release assays (IGRAs) such as the QuantiFERON-TB Gold Plus (QFT-Plus). This study evaluated the association between helminth infections and QFT-Plus results among participants from a TB-endemic region. Methods: A cross-sectional study was conducted from October 2022 to March 2023 in Bahir Dar, Ethiopia. Stool samples of 314 potential participants were examined for helminths using wet mount and Kato-Katz techniques. LTBI was assessed by QFT-Plus from a total of 100 gender-matched helminth-positive and-negative participants. The association between helminth infection status, egg count, and QFT-Plus positivity was analyzed, and p values <0.05 were considered significant. Results: Overall, 53 of 314 screened participants were infected with helminths (16.9%), with A. lumbricoides (47.2%) and hookworm (30.2%) as most prevalent species. The overall QFT-Plus positivity rate was 30.0%, with similar rates observed between helminth-positive and helminth-negative participants. Although QFT-Plus positivity was slightly lower in hookworm carriers (25%) compared to those with A. lumbricoides (32%), a higher-than-median hookworm egg burden was significantly associated with reduced QFT-Plus positivity (P = 0.029). QFT-Plus positivity was significantly higher among male participants than females (P = 0.032). Conclusion: While overall helminth infection status did not significantly affect QFT-Plus positivity, higher hookworm burden was associated with reduced QFT-Plus reactivity. These findings suggest that the type of helminth and infection intensity, rather than its mere presence, may influence IGRA performance. Further studies with larger sample sizes are warranted to understand the species-specific effect of helminth infection on immune modulation of the host.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Ethiopia; intestinal helminths; LTBI; MTB; QFT-Plus